2018
DOI: 10.1136/bcr-2017-224065
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon chronic osteochondral defect in the lateral tibial plateau detected after a separate injury

Abstract: Osteochondral defects (OCD) are rare conditions that usually present in young adolescents. The causes include trauma, inflammation, ischaemia, genetics and changes at secondary ossification centres. The case report presents a 27-year-old man with chronic intermittent left knee pain for about 3 years. He typically develops the symptom after prolonged standing or when rising from a prolonged seated position. An initial MRI scan in 2014 did not identify and report an OCD that was present in his left lateral tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[5] However, some OCDs remain undetected and untreated until later adult life when a poorer prognosis is expected. [6] The most common site for juvenile OCD in the knee is in the posterolateral aspect of the medial femoral condyle. [7,8,9] A study by Hefti et al showed 77% of lesions affected the medial femoral condyle (lateral aspect 51%, central aspect 19% and medial aspect 7%), 17% affected the lateral femoral condyle, 7% affected the patella, 1% affected the trochlea and only 0.2% affected the tibial plateau.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However, some OCDs remain undetected and untreated until later adult life when a poorer prognosis is expected. [6] The most common site for juvenile OCD in the knee is in the posterolateral aspect of the medial femoral condyle. [7,8,9] A study by Hefti et al showed 77% of lesions affected the medial femoral condyle (lateral aspect 51%, central aspect 19% and medial aspect 7%), 17% affected the lateral femoral condyle, 7% affected the patella, 1% affected the trochlea and only 0.2% affected the tibial plateau.…”
Section: Introductionmentioning
confidence: 99%